Father's participation in prenatal care and childbirth: contributions of nurses' interventions - Katherine Souza Vidal Lima; Monalysa Meireles de Barros Carvalho; Tainara Morais Cerqueira Lima; Delmo de Carvalho Alencar; Anderson Reis de Sousa; Álvaro Pereira (Universidad de Antioquia, 2021)
Objective. To describe the discourse of men about participation in prenatal care and childbirth/birth of their children from the contributions made by nurses. Methods. This is an exploratory study, with a qualitative approach, carried out in the wards of a public hospital/maternity hospital in a city in the Northeast, Brazil. Fifty men participated in the study. Data collection with an individual interview, guided by semi-structured script. The data were recorded, transcribed in full, systematized, categorized, and organized by the Collective Subject Discourse method analyzed under the framework of Gender and Masculinities. Result. It was evident in the collective discourse of men that how fatherhood is understood is in transformation, and that the father's participation in the pregnancy and parturition context is under construction. The study showed the change in behavior of men, as well as the expression of new models of masculinities, about the exercise of assisted parenthood motivated by nurses. Conclusion. Nurses' contributions represented necessary elements for greater adherence and male involvement and revealed a possibility to re-signify male identity from the reconstruction of the idea of fatherhood, in the context of pregnancy and parturition.